Penggunaan Media Edukasi Berbasis Card Game Sebagai Upaya Meningkatkan Pengetahuan Dan Sikap Gizi Seimbang Siswa Sekolah Dasar Di Kota Mataram - Siti Azizzah; Agung Kurniawan; Farah Paramita; Septa Katmawanti (Jurnal Medika Nusantara, 2024)
School-aged children are a group that is vulnerable to experiencing nutritional problems (undernutrition and overnutrition). Factors that influence a person's nutrition are a lack of knowledge and attitudes towards balanced nutrition. Providing balanced nutrition education from an early age is a strategy to prevent nutritional problems in school-aged children. Education on balanced nutrition for school-aged children is important because eating habits at this age can influence food preferences and consumption at a later age. This research aims to develop card game-based balanced nutrition education media for students and determine its feasibility and effectiveness in increasing knowledge and attitudes about balanced nutrition. The research method used is the research and development (R&D) method with the ADDIE model. The results of this research are card game-based balanced nutrition education media with a feasibility score of 98.80% for material and 92.26% for media. This media was tested on 40 students with pretest and posttest instruments. The results of statistical tests using the t-test showed that there was a significant influence on the use of the Gimbang Game educational media on increasing knowledge and attitudes towards balanced nutrition among students at SDN 32 Ampenan, Mataram City with a significance result of ?=0.000 (?<0.005).